Nitric oxide role and endothelial dysfunction development in diabetes mellitus - S. G. Dzugkoev; F. S. Dzugkoeva; V. A. Metelskaya (Кардиоваскулярная терапия и профилактика)
The review presents the modern views on the mechanisms resulting in endothelial dysfunction, macro- and microangiopathy among patients with diabetes mellitus (DM). The role of nitric oxide (NO) in these mechanisms, NO input in the pathogenesis of vascular DM complications, and the effects of DM-related metabolic disturbances on NO bioavailability are discussed.